El relato histórico y el mito en Rosa Cuchillo - Rojas Prudencio, Hardy (2016)
Rosa Cuchillo, novel of the peruvian writer Oscar Colchado Lucio, treats about the terrorism in the eighties decade. The important aspect about the text is the andean perspective about the violence against the runa. Colchado proposes an opened andean point of view, capable to talk and find things in common with the Other. In Rosa Cuchillo, the quechua culture is part of the solution, not the problem. In order to do that, the author constructs two antagonic characters: Inkarri and the pishtaco or nakaq. The first one is represented by Liborio, the second, by Sendero Luminoso and the peruvian government. The author creates tension among both characters, that produces crisis in the andean world. In order to solve the conflict, Liborio proposes an alternative way that involves Sendero. We want to focus on the construcción of both characters. We affirm that the author uses the historic story and the myth in order to create the cultural hero of the text. In the case of Liborio, we can identify elements of the Atahualpa, Tupac Amaru I and Tupac Amaru II stories. By the other hand, we can find the pishtaco or nakaq story in the prehispanic time. We will see how the nakaq concept gets new meanings in crisis times.